Viscoelastic Effects on Free Convective Three-Dimensional Flow with Heat and Mass Transfer. (29th February 2012) - Choudhury, Rita; Das, Utpal Jyoti
Abstract : A theoretical study of free convective three-dimensional heat and mass transfer flow of a viscoelastic fluid along a steadily moving porous vertical plate in presence of transverse sinusoidal suction velocity distribution, and uniform free stream velocity has been considered. The flow becomes three dimensional due to this suction velocity. The governing equations of the flow field are solved by using series expansion method, and the expressions for velocity field, temperature field, skin friction, heat flux in terms of Nusselt number, and mass flux in terms of Sherwood number are obtained. The effects of the viscoelastic parameter on velocity profiles and shear stress with the combination of the other flow parameters are discussed graphically.